Tsunami Hazard Analysis in Likupang Tourism Area, North Sulawesi - Saputri, Febriani; Angmalisang, Ping Astony; Pelle, Wilmy Etwil; Manembu, Indri; Rumengan, Anton; Bara, Robert; Sumilat, Deiske (International journal of Rural Development, Environment and Health Research, 2023)
The Likupang area, North Sulawesi is one of the super priority tourist destinations launched by the Central Government with the marine tourism sector as the axis. On the other hand, the potential for natural disasters originating from the sea is unavoidable so it needs to be one of the considerations in the process of developing disaster-responsive tourist areas. A tsunami hazard analysis study is first step in disaster mitigation planning. The study is in the form of tsunami modeling by identifying the worst possible scenario in the Likupang area using COMMIT modeling. The modeling is able to produce parameters such as arrival time, maximum height and tsunami inundation area. These three parameters are used as the basis for mapping the tsunami hazard map. The modeling produces the fastest arrival time, which occurs in the first minute after an earthquake occurs. The maximum height obtained from the modeling is 6.8 meters. The maximum inundation area reached by the tsunami wave is 23.57 km2. The combined results of the five scenarios are presented in hazard maps. The majority of public tourist sites are in the Warning status area, but some private resorts are still in the area with the Major Warning status.